Prediction of transient NOx emissions from a non-road heavy-duty diesel engine based on GWO-RF algorithm - Zhenkai Tang; Lili Lei; Hongyu Zhao; Haojie Qi; Pan Wang (Fuel, 2026)

Magnetic biochar-enhanced electron transfer in pyrite-based biofilm electrode reactor: Mechanisms of preparation method and mass ratio - Qinglong Wang; Boling Huang; Lili Dai; Liang Peng; Shiyang Zhang; Lingwei Kong; Hongyu Wang; Xinhua Tang; Hui Zhang (Chemical Engineering Journal, 2026)

An appearance-independent multi-object tracking framework for group-housed pigs - Liwen Chen; Lu Yang; Jianzhai Wu; Xiangfang Tang; Guodong Cheng; Hongyu Zhang; Jianyu Fang; Chao Ma; Shuqing Han (Computers and Electronics in Agriculture, 2026)

Window-specific effects of ultraviolet radiation and air pollution on ovarian reserve in infertile women: A retrospective cohort study - Qi Tang; Cong Fu; Hongyu Du; Qing Liu; Kui Yang; Zhuoni Xiao; Yanqing Xu (Environmental Pollution, 2026)

Lateral cyclic response and probabilistic design framework for monopile foundations in spatially variable clay - HongYu Tang; Zhen Wang; XiaoBin Li; HaiXiu Sun; JiangTao Yi; Fei Liu (Computers and Geotechnics, 2026)

Evaluating ERA5-Land air temperature and dew point biases in built-up environments in the UK - Junjie Yu; Wenyuan Li; Lingcheng Li; Divya Kumar; Hongyu Sun; David O. Topping; Guoqiang Tang; Zhonghua Zheng (Urban Climate, 2026)

Facet-dependent N2O decomposition over morphology controlled Co3O4 catalyst - Hongyu Zhao; Pan Wang; Zonglin Li; Haojie Qi; ZhenKai Tang; Lili Lei (Fuel, 2026)

Exogenous additives for acrylamide mitigation in thermally processed foods: A review of safety risks and quality impacts - Yang Hongyu; Yin Hongling; Li Xiaolin; Tang Hongtao; Yang Siyue; Luo Liyong; Zeng Liang; Luo Wei (Food Chemistry, 2026)

Pneumatic-structural coupled response of flexible ventilated skirts for air-cushion vehicles under wave-induced heave excitation - Hongyu Zhuang; Shengjie Xu; Yuchao Yuan; Wenyong Tang (Ocean Engineering, 2026)

Machine learning - optimized molecularly imprinted electrochemical sensor based on Bi-rich BiOBr/BC@AuNPs for trace determination of sulfachlorpyrazine sodium in food - Qian Zeng; Peng Liu; Yihui Chen; Yingnan Li; Hongyu Xiao; Qingwei Li; Anna Li; Jingye Liang; Weiqiang Li; Yangping Wen; Kaijie Tang (Food Chemistry, 2026)

Microbial carbon use efficiency, not extracellular enzyme stoichiometry, shows negligible response to alpine tunnel construction - Jiarui Tian; Yan Yue; Hongyu Lin; Yixuan Cheng; Yuzhuo Chen; Jincheng Xiang; Benjamin Laffitte; Xiangjun Pei; Xiaolu Tang (Journal of Environmental Management, 2026)

Polylactic acid microplastics regulate organophosphorus pesticide impacts on phosphorus bioavailability in soil-plant systems - Gaowei Tan; Lingling Ding; Darrell W.S. Tang; Yan Wang; Jing Yang; Hongyu Mu; Xiaomei Yang (Journal of Hazardous Materials, 2026)

Ultra-high-temperature pyrolysis of end-of-life tires for clean metallurgical reduction: A sustainable waste-to-resource pathway - Enze Shi; Jue Tang; Mansheng Chu; Hongyu Tian (Journal of Environmental Chemical Engineering, 2026)

Pre-molt cholesterol regulation of ecdysone receptor (EcR) signaling in the Y-organ contributes to dietary control of molting in Scylla paramamosain - Shichao Xie; Yao Deng; Yinqiu Tian; Zheng Tang; Tiantian Xu; Xiaoyue Li; Wenhao Zhan; Hongyu Peng; Yangguang Bao; Tingting Zhu; Wenli Zhao; Min Jin; et al. (Insect Biochemistry and Molecular Biology, 2026)

Long-term HRV metrics may assist in differentiating between prolonged disorders of consciousness and emergence from minimally conscious state : a cross-sectional study - Xinwei Tang; Na Ren; Zuojun Cao; Zi Yu; Xu Han; Weiqiang Cai; Youbei Yang; Lisi Lu; Mukedaisihan Maisedi; Zuowen Sun; Junfa Wu; Yi Wu; et al. (Acta Neurologica Belgica, 2026)

Revealing the anomalous 2025 green tide trajectory in the Southern Yellow Sea using multi-source satellite imagery and VB-FAH - Hongyu Kan; Mengquan Wu; Longxing Liu; Hao Wu; Jie Zhao; Lina Ren; Gang Chen; Yijie Tang; Jinyi Lv; Jun Zhao (Marine Pollution Bulletin, 2026)

Axial cyclic bearing characteristics and predictive analysis of displacement accumulation for monopile foundations in soft clay: Experimental and numerical investigation - HongYu Tang; HaiXiu Sun; JiangTao Yi; JingNian Ran; ChangBing Qin (Ocean Engineering, 2026)

Surface modification of ferrous sulfide nanosheets for in-situ remediation of cadmium-contaminated groundwater - Huagang Lv; Ying Liang; Lu Tang; Hongyu Liu; Wen Zhang; Kaihua Bai; Jun Jiang (Journal of Environmental Sciences, 2026)

Unveiling the co-occurrence of fluoride-arsenic and nitrate retention in Wujiang cascade reservoirs by a hybrid hydrochemical, PMF model and multi-isotopic method - Tianna Zhang; Hongbo Wang; Leyan Feng; Hongyu Tang; Jiaju Liu; Ting Wang (Environmental Pollution, 2026)

A remote sensing framework unveiling the life-cycle dynamics and environmental drivers of Ulva prolifera green tides in the South Yellow Sea - Yijie Tang; Mengquan Wu; Jie Zhao; Shaopeng Luan; Pengsen Yang; Longxing Liu; Bowen Liu; Jinyi Lv; Gang Chen; Hongyu Kan; Yuying Ran; Huining Lai (Marine Environmental Research, 2026)

Efficiencies and mechanisms of mixed magnetic resins coupled with ozonation for removing diverse pollutants from secondary effluent for landscape reuse - Yingcai Tang; Shuailin Xin; Hongyu Yang; Lixin Ma; Weirong Liu; Huanyu Bao; Baozhen Liu; Yunze Ruan (Journal of Environmental Chemical Engineering, 2026)

Fabricating nano- and micro- pesticide delivery systems using environmentally friendly humic acid - Kun Zhuang; Yue Xu; Zijun Wang; Xin Liu; Yunyu Tang; Xiangyang Li; Guang Wei; Hongyu Cao; Tingting Zhai; Feng Liu; Nan Zou; Peng Zhang; et al. (Chemical Engineering Journal, 2026)

How urban sprawl patterns shape the thermal environment during hot summers: An empirical analysis of 338 Chinese cities - Yifeng Ji; Zhitao Li; Ying Liu; Hongyu Tang; Hao Sun; Tao Feng (Environmental Impact Assessment Review, 2026)

A high-dielectric additive for enhanced supercapacitor performance with N-doped carbon electrodes - Hongyu Liang; Hui Li; Shengda Tang; Jiahui Li; Zhaomin Zhu; Li Pan; Yongfeng Bu (Chemical Engineering Journal, 2026)

Linking scales for asphalt-mineral interface failure mechanism: Insights from molecular tension simulation, macro pull-off experiments, and verified finite element analysis - Guoqing Sun; Hongyu Wang; Jiupeng Zhang; Yan Li; Qiang Tang; Wei Liu (Fuel, 2026)

From fat to fate: how aging adipose tissue drives systemic metabolic aging - Haiyan Lin; Hongyu Li; Qiang Tang (Biogerontology, 2026)

Low-dose astaxanthin promotes growth via bile acid-regulated metabolic and lipid-antioxidant pathways in Scylla paramamosain - Yao Deng; Shichao Xie; Wenhao Zhan; Tingting Zhu; Hongyu Peng; Haiqing Cao; Zheng Tang; Xiaoyue Li; Tiantian Xu; Min Jin; Qicun Zhou (Aquaculture, 2026)

CEL method-based numerical analysis on hydrodynamic load and response of skirt inclined water entry for air-cushion vehicles under venting conditions - Hongyu Zhuang; Shengjie Xu; Yuchao Yuan; Wenyong Tang (Ocean Engineering, 2026)

Investigation of the aggregation and assembly mechanisms of trace organic compounds and dissolved organic matter using a combined approach of molecular dynamics simulations and experiments - Yingcai Tang; Shuailin Xin; Liyu Xu; Hongyu Yang; Peiyan Sun; Lixin Ma; Weirong Liu; Huanyu Bao; Baozhen Liu; Yunze Ruan (Journal of Environmental Management, 2026)

Multi-scale insights into steel slag-derived dual functional materials for enhanced hydrogen production and CO2 capture in biomass sorption-enhanced gasification - Hongyu Liu; Yuting Tang; Xiaoqian Ma; Jiehong Tang; Wenchang Yue; Zhuofan Chen; Zejie Zheng (Fuel, 2026)

The characteristics and prognostic analysis of therapy-related acute myeloid leukemia patients in China - Feifei Tang; Yunqi Wang; Yu Zhang; Hongyu Zhang; Jinhai Ren; Pengcheng He; Yajing Xu; Hua Yan; Yongqian Jia; Liping Dou; Tao Wu; Zhi Guo; et al. (Science China Life Sciences, 2026)

Research on Hydraulic Fracture Cross-layer Propagation and Bedding Plane Activation in Artificial Layered Rock Fracturing: Insight from Physical Experiments - Hongyu Xian; Peng Zhao; Haiyan Zhu; Lei Tao; Xuanhe Tang; Ming Lei (Rock Mechanics and Rock Engineering, 2026)

Mechanical behavior of surface conductors induced by drill string vibrations during deepwater drilling - Qishuai Yin; Jingxuan Tang; Zengcheng Han; Yao Zhou; Hongyu Wan; Yongqi Ma (Ocean Engineering, 2025)

Anthropogenic aerosol feedbacks intensify air pollution and weather variability over China - Jixiang Li; Haipeng Yu; Andrea Pozzer; Kai Tang; Chenhui Jia; Zeyong Hu; Siyu Chen; Yunsai Zhu; Yuling Hu; Bofei Zhang; Hongyu Luo; Zekui Jiang; et al. (Atmospheric Environment, 2025)

Projections of Autumn Precipitation Extremes in Southwest China Based on a Statistically Downscaled CMIP6 Dataset - Linxiao Wei; Hongyu Tang; Yong Wang; Yao Wu; Tianyu Zhang; Qilin Li; Jie Zhou; Fen Zhang; Wanhong Li; Tan’anbang Lyu (Journal of Meteorological Research, 2025)

Gradual succession of dominant pathway from autotrophic to heterotrophic metabolism with the increment of C/N in pyrite-based biofilm-electrode reactor (PBER) - Lin Tan; Zhiyuan Wang; Hongyu Wang; Shiyang Zhang; Wenjiao Sang; Qian Zhang; Xinhua Tang; Qianjin Dong (Environmental Research, 2025)

Metagenomic analysis of algal-bacteria symbiosis system (ABSS) under aniline stress: Synergistic optimization of aniline degradation and nitrogen metabolism - Xiaoqian Dong; Qian Zhang; Meng Li; Naif Abdullah Al-Dhabi; Jiajing Chen; Jing He; Hongyu Wang; Wangwang Tang (Environmental Research, 2025)

The SDGSAT-1 mission and its role in monitoring SDG indicators - Huadong Guo; Changyong Dou; Dong Liang; Bihong Fu; Hongyu Chen; Ziming Zou; Peng Huang; Xiaoming Li; Fansheng Chen; Chengshan Han; Juanjuan Jing; Tai Hu; et al. (Remote Sensing of Environment, 2025)

Formation and slamming response characteristics of flexible skirts in air-cushion vehicles under venting conditions - Hongyu Zhuang; Shengjie Xu; Yuchao Yuan; Wenyong Tang (Ocean Engineering, 2025)

Application of CaO-Ni bifunctional material in the adsorption - enhanced pyrolysis of municipal solid waste - Haohang Huang; Yuting Tang; Hongyu Liu; Jiehong Tang; Ziwei Sun; Zejie Zheng; Xiaoqian Ma (Journal of Environmental Chemical Engineering, 2025)

Modulation of strategic status signaling: oxytocin changes men’s fluctuations of status products preferences in their female partners’ menstrual cycle - Honghong Tang; Hongyu Fu; Song Su; Luqiong Tong; Yina Ma; Chao Liu (Psychopharmacology, 2025)

Wavelength-selective synaptic devices based on Graphdiyne/WSe2 for multi-color image recognition and neuromorphic computing - Hongyu Tang; Weiqi Shi; Wanlin Jiang; Gaoyuan Wang; Mengyuan Tang; Zihao Cai; Ruiteng Li; Shuai Wu; Guoqi Zhang; Jian Li (Chemical Engineering Journal, 2025)

Dietary hydroxymethionine-chelated manganese improved growth and Mn deposition, regulated lipid metabolism and enhanced antioxidant capacity by reducing endoplasmic reticulum stress and autophagy for juvenile Litopenaeus vannamei - Shuqin Li; Hongyu Peng; Min Jin; Lu Zhang; Jinlin Wang; Yu He; Chaokai Huang; Yushan Zou; Xiaoru Chen; Yinzhao Zhang; Feng Tang; Qicun Zhou (Aquaculture, 2025)

Middle Triassic humidification in Southern North China linked to northward propagation of Qinling Orogenic Belt - Wentao Yang; Wenguang Tang; Jianghai Yang; Hongyu Zhang; Yuansheng Du (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Stratified strategies for enhancing thermal comfort through multidimensional compactness optimization in urban built-up areas during heatwaves - Yifeng Ji; Ying Liu; Hongyu Tang; Zhitao Li; Yihang Bai; Tao Feng (Sustainable Cities and Society, 2025)

Multi-omics analysis revealed the effects of different astaxanthin sources on the antioxidant properties of Scylla paramamosain - Yao Deng; Wenhao Zhan; Shichao Xie; Hongyu Peng; Haiqing Cao; Zheng Tang; Yinqiu Tian; Tingting Zhu; Peng Sun; Min Jin; Qicun Zhou (Food Chemistry, 2025)

Experimental research and application of a new no-pillar green coal mining method - Qiang Fu; Jun Yang; Yubing Gao; Hongxu Song; Yuxuan Liu; Hongyu Jin; Jiarui Tang; Junpeng Zhao; Jianbo Cui (Bulletin of Engineering Geology and the Environment, 2025)

Self-assembled TMB-CuO2 nanosheets for dual-mode colorimetric and NIR-II photothermal detection of uranyl ion - Yingying Wu; Xiaofeng Tan; Hongyu Gong; Minghui Wang; Gui-long Wu; Na Li; Fen Liu; Hong Xia; Li Tang; Qinglai Yang (Analytica Chimica Acta, 2025)

Hypoxic breast cancer cell-derived exosomal miR-143-3p targets RICTOR to regulate M2 macrophage polarization, thereby modulating cancer cell invasiveness - Hongyu Lian; Miao Yu; Qi Li; Jiayi Xiao; Xin Tang; Bin Zhang; Dongxue Liu; Yongliang Xu; Mo Dong; Zitao Li; Lihong Yao; Caijuan Li (Human Cell, 2025)

Enhanced methanogenesis and efficient ciprofloxacin degradation via nZVI@LDH in an electricity-driven anaerobic bioreactor: A biotic-abiotic hybrid system for ROS regulation and ARGs mitigation - Jinfeng Chen; Yi Tang; Xinyan Chen; Junlan Chen; Zhang Yan; Xiao Yao; Hongyu Zhang; Yanyan Pei; Zhuwu Jiang (Journal of Hazardous Materials, 2025)

Co-occurrence of multiple contaminants: Unentangling adsorption behaviour in agricultural soils - Gaowei Tan; Darrell W.S. Tang; Vera Silva; Hongyu Mu; Shijie Qin; Osman Rima; Violette Geissen; Xiaomei Yang (Environmental Pollution, 2025)

Application of extreme gradient boosting for predicting standard penetration test N-values from cone penetration test data - Xiao Han; Jiangtao Yi; Xiaobin Li; Siyu Li; Hongyu Tang; Zhen Wang; Jingnian Ran (Bulletin of Engineering Geology and the Environment, 2025)

Neuronal Injury after Ischemic Stroke: Mechanisms of Crosstalk Involving Necroptosis - Xuanning Zhang; Hongyu Li; Yaowei Zhao; Tingting Zhao; Zhihao Wang; Qiang Tang (Journal of Molecular Neuroscience, 2025)

Exploring the effect of new urban expressway on travel time - Tianjiao Chen; Luliang Tang; Zilong Zhao; Hong Yang; Xiaogang Guo; Hongyu Shi (Journal of Transport Geography, 2025)

Aging through the lens of mitochondrial DNA mutations and inheritance paradoxes - Jia Chen; Hongyu Li; Runyu Liang; Yongyin Huang; Qiang Tang (Biogerontology, 2025)

Impact of land covers on pesticide contamination and the associated ecological risk in a major tributary of the Pearl River, South China - Kaiyi Wu; Qilong Liao; Chengzhong Fu; Weikeng Luo; Qiyuan Lu; Bowen Li; Hongyu Fu; Zhongwen Li; Guangyu Liao; Bin Tang; Jing Zheng (Science of The Total Environment, 2025)

An AI-driven electromagnetic-triboelectric self-powered and vibration-sensing system for smart transportation - Minfeng Tang; Zheng Fang; Chengliang Fan; Zutao Zhang; Lingji Kong; Hongyu Chen; Zhenhua Zeng; Yun Yang; Lingfei Qi (Engineering Structures, 2025)

Traditional Chinese medicine combined with chemotherapy in the treatment of advanced non-small cell lung cancer: key drug screening and mechanism analysis - Yu Tang; Zhengping Xian; Fengjiao Wu; Hongyu Cao; Lihao Wang; Qian Tang; Yanan Du; Xuefang Zheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Dietary cholesterol promotes the growth of mud crabs, Scylla paramamosain by regulating cholesterol metabolism, enhancing ecdysteroid synthesis and molting cascade response - Shichao Xie; Wenhao Zhan; Hongyu Peng; Yao Deng; Zheng Tang; Haiqing Cao; Tingting Zhu; Yuedong Shen; Wenli Zhao; Qicun Zhou; Min Jin (Animal Feed Science and Technology, 2025)

A Machine Learning-Based Observational Constraint Correction Method for Seasonal Precipitation Prediction - Bofei Zhang; Haipeng Yu; Zeyong Hu; Ping Yue; Zunye Tang; Hongyu Luo; Guantian Wang; Shanling Cheng (Advances in Atmospheric Sciences, 2025)

Dietary arachidonic acid supplementation promoted cholesterol utilization, lipid deposition and molting for Scylla paramamosain - Shichao Xie; Yao Deng; Zheng Tang; Yinqiu Tian; Haiqing Cao; Wenhao Zhan; Tingting Zhu; Yuedong Shen; Wenli Zhao; Hongyu Peng; Min Jin; Qicun Zhou (Aquaculture, 2024)

Chlamydia psittaci infection induces IFN-I and IL-1β through the cGAS-STING-IRF3/NLRP3 pathway via mitochondrial oxidative stress in human macrophages - Hongyu Yang; Peiyuan Sun; Shi Zhou; Yuanyuan Tang; Sijia Li; Weiwei Li; Xiang Yu; Hanying Liu; Yimou Wu (Veterinary Microbiology, 2024)

Preparation of nano-Al2O3 support CaO-based sorbent pellets by novel methods for high-temperature CO2 capture - Weilong Chen; Yuting Tang; Hongyu Liu; Jiehong Tang; Jingmin Deng; Ziwei Sun; Xiaoqian Ma (Journal of Environmental Chemical Engineering, 2024)

How do heat waves affect the relationship between built environment patches of different compactness and land surface temperature? - Yifeng Ji; You Peng; Hongyu Tang; Zhitao Li; Yiting Xia; Tao Feng (Building and Environment, 2024)

Advancements in modifying insoluble dietary fiber: Exploring the microstructure, physicochemical properties, biological activity, and applications in food industry—A review - Tong Liu; Hongyu Lei; Xinyu Zhen; Jiaxing Liu; Wenlong Xie; Qilong Tang; Dongxia Gou; Jun Zhao (Food Chemistry, 2024)

Mechanism influence on the coexistence of two anions on redox kinetics and volume effect of CoPSe as anode material for potassium-ion batteries and potassium-ion hybrid capacitors - Xiujuan Wang; Jiamei Wang; Yingying Wang; Ruihao Chen; Jing Qin; Tang Ouyang; Hongyu Wei; Hao Jing; Guanghui Yuan; Beibei Wang; Gang Wang (Chemical Engineering Journal, 2024)

The next-generation of metaverse embodiment interaction devices: A self-powered sensing smart monitoring system - Ning Yang; Chengliang Fan; Hongyu Chen; Minfeng Tang; Junwei Hu; Zutao Zhang (Chemical Engineering Journal, 2024)

Red mud enhanced biomass gasification to produce syngas: Mechanism, simulation and economic evaluation - Hongyu Liu; Yuting Tang; Xiaoqian Ma; Jiehong Tang; Wenchang Yue; Weilong Chen; Ziwei Sun; Jingmin Deng (Chemical Engineering Journal, 2024)

Fatigue damage evolution behaviors and fractional fatigue mechanical model of monzogabbro under true triaxial disturbance test - Zhi Zheng; Hongyu Xu; Wei Wang; Guoxiong Mei; Wuqiang Cai; Zhi Tang; Zhiyang Cai (International Journal of Rock Mechanics and Mining Sciences, 2024)

Vitamin C as a functional enhancer in the non-specific immune defense, antioxidant capacity and resistance to low-temperature stress of juvenile mud crab, Scylla paramamosain - Zheng Tang; Shichao Xie; Yuhui Cui; Wenhao Zhan; Yao Deng; Hongyu Peng; Haiqing Cao; Yinqiu Tian; Min Jin; Peng Sun; Yingzhao Zhang; Feng Tang; et al. (Fish & Shellfish Immunology, 2024)

Polymer hydrogel electronics with adhesive, self-healing, and anti-ultraviolet capabilities for machine learning-promoted electrophysiological detection - Congcong Yang; Gege He; Bo Xu; Hongyu Mi; Fengjiao Guo; Yan Tang; Chunjiang Jin; Jieshan Qiu (Chemical Engineering Journal, 2024)

Future changes in extremes across China based on NEX-GDDP-CMIP6 models - Yang Baogang; Wei Linxiao; Tang Hongyu; Li Yonghua; Wang Yong; Zhang Fen; Zhou Jie; Zhang Tianyu; Lv Tananbang (Climate Dynamics, 2024)

The influence of sex-specific factors on biological transformations and health outcomes in aging processes - Yongyin Huang; Hongyu Li; Runyu Liang; Jia Chen; Qiang Tang (Biogerontology, 2024)
The aging process demonstrates notable differences between males and females, which are key factors in disease susceptibility and lifespan. The differences in sex chromosomes are fundamental to the presence of sex bias in organisms. Moreover, sex-specific epigenetic modifications and changes in sex hormone levels impact the development of immunity differently during embryonic development and beyond. Mitochondria, telomeres, homeodynamic space, and intestinal flora are intricately connected to sex differences in aging. These elements can have diverse effects on men and women, resulting in unique biological transformations and health outcomes as they grow older. This review explores how sex interacts with these elements and shapes the aging process.

Microplastic pollution differences in freshwater river according to stream order: Insights from spatial distribution, annual load, and ecological assessment - Weikeng Luo; Hongyu Fu; Qiyuan Lu; Bowen Li; Xue Cao; Sifan Chen; Ruijuan Liu; Bin Tang; Xiao Yan; Jing Zheng (Journal of Environmental Management, 2024)

Dietary lauric acid promoted antioxidant and immune capacity by improving intestinal structure and microbial population of swimming crab (Portunus trituberculatus) - Wenhao Zhan; Hongyu Peng; Shichao Xie; Yao Deng; Tingting Zhu; Yuhui Cui; Haiqing Cao; Zheng Tang; Min Jin; Qicun Zhou (Fish & Shellfish Immunology, 2024)

Experimental Study on an Innovative Method for Pre-split Blasting to Protect Withdrawal Roadways - Jun Yang; Xing Wu; Qiang Fu; Shilin Hou; Hongxu Song; Hongyu Jin; Yuxuan Liu; Jiarui Tang (Rock Mechanics and Rock Engineering, 2024)

Application of CRISPR/Cas12a in miRNA-155 detection: A novel homogeneous electrochemiluminescence biosensor - Yuanxun Gong; Hongyu Zeng; Sisi Gao; Yanlin He; Jie Wang; Jihua Wei; Qianli Tang; Kai Zhang; Xianjiu Liao (Analytica Chimica Acta, 2024)

National-scale 10 m annual maize maps for China and the contiguous United States using a robust index from Sentinel-2 time series - Yingze Huang; Bingwen Qiu; Peng Yang; Wenbin Wu; Xuehong Chen; Xiaolin Zhu; Shuai Xu; Laigang Wang; Zhanjie Dong; Jianyang Zhang; Joe Berry; Zhenghong Tang; et al. (Computers and Electronics in Agriculture, 2024)

Ferroptosis: a critical mechanism of N6-methyladenosine modification involved in carcinogenesis and tumor progression - Qingqing Wei; Changning Xue; Mengna Li; Jianxia Wei; Lemei Zheng; Shipeng Chen; Yumei Duan; Hongyu Deng; Faqing Tang; Wei Xiong; Ming Zhou (Science China Life Sciences, 2024)

Effect of mPEG-PLGA on Drug Crystallinity and Release of Long-Acting Injection Microspheres: In Vitro and In Vivo Perspectives - Dandan Xing; Lihua Tang; Hongyu Yang; Mingjiao Yan; Panao Yuan; Yulan Wu; Yu Zhang; Tian Yin; Yanjiao Wang; Jingxin Gou; Xing Tang; Haibing He (Pharmaceutical Research, 2024)

Effect of Nitrate Concentration on Anaerobic Methane Oxidation Coupled to Denitrification in Membrane Biofilm Reactor After Prolonged Storage - Wei Zhang; Yibo Zhao; Jing Wang; Yang Gao; Lean Zhou; Shiquan Sun; Meiyi Tang; Yazhou Peng; Wenbing Guo; Hongyu Wang (Water, Air, & Soil Pollution, 2024)

New directions on membranes for removal and degradation of emerging pollutants in aqueous systems - Die Ling Zhao; Wangyi Zhou; Liguo Shen; Bowen Li; Hongyu Sun; Qianqian Zeng; Chuyang Y. Tang; Hongjun Lin; Tai-Shung Chung (Water Research, 2024)

Evaluation and Projection of Extreme High Temperature Indices in Southwestern China Using NEX-GDDP-CMIP6 - Fen Zhang; Linxiao Wei; Yonghua Li; Hongyu Tang; Tianyu Zhang; Baogang Yang (Journal of Meteorological Research, 2024)

Integrative analysis of health restoration in urban blue-green spaces: A multiscale approach to community park - Jiangjun Wan; Hongyu Wu; Rebecca Collins; Kuntao Deng; Wei Zhu; Hai Xiao; Xiaohong Tang; Congshan Tian; Chengyan Zhang; Lingqing Zhang (Journal of Cleaner Production, 2024)

Enhancing electricity-driven methanogenesis by assembling biotic-abiotic hybrid system in anaerobic membrane bioreactor - Zhuwu Jiang; Yi Tang; Xinyan Chen; Xueming Chen; Haoshuai Wang; Hongyu Zhang; Chaoqun Zheng; Jinfeng Chen (Bioresource Technology, 2024)

Global burden of leukemia attributable to occupational exposure to formaldehyde from 1990 to 2019 - Ying Xu; Yuqi Liu; Hongyu Sun; Xingyu Gong; Guanghui Yu; Chunxia Zhai; Wanqin Hu; Qiqun Zong; Yingying Yu; Yuqin Tang; Mingyi Zhang; Fang Wang; et al. (Environmental Science and Pollution Research, 2023)

Holocene Evolution of the Pearl River Delta: Mapping Integral Isobaths and Delta Progradation - Yongjie Tang; Zhuo Zheng; Kangyou Huang; Cong Chen; Zhen Chen; Hongyu Lu; Weisheng Wu; Xiaoming Lin; Xianhe Zhang; Hongwei Li (Journal of Marine Science and Engineering, 2023)
The Pearl River Delta (PRD, China) has undergone complex geological development within a multi-island faulted basin, shaped by the interplay of regional tectonic movements, Quaternary sea-level fluctuations, and fluvial-marine interactions. Despite a great number of studies on the Holocene sedimentary sequences and spatial differences of lithofacies and environments, scant attention has been paid to the overarching human influence on deltaic evolution and coastline modifications since the Neolithic epoch. To further elucidate the spatial variation in Holocene sedimentation and its underlying basement topography shaped during the Last Glacial Maximum (LGM), we compiled a comprehensive dataset incorporating borehole data from over 2800 cores (the maximum depth can reach 92.5 m) within the PRD. Subsequently, high-resolution isobath maps of Quaternary deltaic deposits were generated, offering unprecedented insights into sediment distribution. This dataset facilitated a nuanced reconstruction of pre-Holocene topography, revealing a zone characterized by elongated, deep-incised valleys governed by NW-SE fault orientations. Further, we delineated coastline shifts since the period of maximum Holocene transgression (~7000 years BP), contributing to an enhanced understanding of the formation and evolutionary patterns of the delta and river network oscillations. Our findings illuminate an increasing anthropogenic impact on the rate of fluvial sedimentation and land growth, particularly accentuated over the last two millennia, favoring deltaic accretion.

Manufacturing industry relocation trends from the perspective of field theory: The case of the belt and road Sino-Europe economic corridor - Hongyu Tang; Yonglei Jiang; Zixuan Peng; Yazhi Liu; Bin Yu (Ocean & Coastal Management, 2023)

Boron nitride aerogels incorporated with metal nanoparticles: Multifunctional platforms for iodine capture and detection - Gen Li; Jianli Liang; Jing Lin; Hongyu Li; Yan Liu; Guoyang Xu; Chao Yu; Zhonglu Guo; Chengchun Tang; Yang Huang (Journal of Hazardous Materials, 2023)

Weak persistence of Northwest Pacific anomalous anticyclone during post-El Niño summers in CMIP5 and CMIP6 models - Haosu Tang; Gang Huang; Kaiming Hu; Wenping Jiang; Weichen Tao; Ya Wang; Hongyu Hou (Climate Dynamics, 2023)

Full life circle of micro-nano bubbles: Generation, characterization and applications - Jianguang Jia; Zhaoxu Zhu; Hao Chen; Hongyu Pan; Long Jiang; Wen-Hao Su; Qiang Chen; Yingwen Tang; Jianming Pan; Kai Yu (Chemical Engineering Journal, 2023)

Overview of a Sleep Monitoring Protocol for a Large Natural Population - Minghui Liu; Hangyu Zhu; Jinbu Tang; Hongyu Chen; Chen Chen; Jingchun Luo; Wei Chen (Phenomics, 2023)

Ecological risk assessment of pesticides on soil biota: An integrated field-modelling approach - Hongyu Mu; Xiaomei Yang; Kai Wang; Darrell Tang; Wen Xu; Xuejun Liu; Coen J. Ritsema; Violette Geissen (Chemosphere, 2023)

Joint effect of ambient PM2.5 exposure and vitamin B12 during pregnancy on the risk of gestational diabetes mellitus - Xueli Yang; Qiang Zhang; Yao Sun; Chen Li; Hongyu Zhou; Chang Jiang; Jing Li; Liwen Zhang; Xi Chen; Naijun Tang (Science of The Total Environment, 2023)

Effective biocontrol of soybean root rot by a novel bacterial strain Bacillus siamensis HT1 - Haitao He; Qianhang Zhai; Yanan Tang; Xuehu Gu; Hongyu Pan; Hao Zhang (Physiological and Molecular Plant Pathology, 2023)

Correction of sub-seasonal predictions of summer precipitation in Southwest China based on the Transformer-Seq2Seq-DNN ensemble deep learning model - Qu Guo; Fei Luo; Hongyu Tang; Yonghua Li (Theoretical and Applied Climatology, 2023)

Assessing the visibility of urban greenery using MLS LiDAR data - Liyu Tang; Jianguo He; Wei Peng; Hongyu Huang; Chongcheng Chen; Can Yu (Landscape and Urban Planning, 2023)

Simulation and projection of climate extremes in China by multiple Coupled Model Intercomparison Project Phase 6 models - Linxiao Wei; Xiaoge Xin; Qilin Li; Yao Wu; Hongyu Tang; Yonghua Li; Baogang Yang (International Journal of Climatology, 2023)
This study evaluates the ability of 23 climate models from phase 6 of the Coupled Model Intercomparison Project (CMIP6) in simulating extreme climate events over China. The multimodel ensemble (MME) performs better than most individual models in reproducing the climatological mean distribution of all extreme indices. The MME can reproduce well the climatological mean distributions of five extreme climate indices over China, including annual total precipitation (PTOT), maximum consecutive 5‐day precipitation (RX5), simple daily intensity (SDII), maximum daily maximum temperature (TXX), and minimum daily minimum temperature (TNN), with Taylor skill scores exceeding 0.7. SDII and TXX are the most skilful precipitation and temperature extreme indices simulated by the MME, respectively. The MME has relatively lower skill in simulating the climatological mean distribution of warm days (TX90P) and cold nights (TN10P) over China. Future projections of these extreme climate indices by the end of the 21st century are explored with the MME under the SSP1‐2.6, SSP2‐4.5, and SSP5‐8.5 scenarios. The PTOT and RX5 in northwestern China are all projected to increase by more than 30% under SSP5‐8.5. R20 is projected to increase by 4–5 days over southeastern China under SSP5‐8.5. There are fewer (more) consecutive dry days over north China (south China), with a change of 5 days under SSP5‐8.5. The extreme temperature indices, including TX90P, TXX, and TNN, all increase with time and higher SSP scenarios. The three indices increase by 40–55%, 4–6°C, and 4–7°C under SSP5‐8.5 over east China, respectively. The TN10P decreases by more than 6% over east China. The changes in these extreme indices under SSP1‐2.6 and SSP2‐4.5 are similar to those under SSP5‐8.5 but with a smaller magnitude. Large uncertainties still exist in the future projections, especially under the high SSP scenarios.

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Cr(VI) removal from contaminated waters using ultra-thin layered meixnerite - Yaowu Cao; Qinghai Guo; Zheyan Miao; Baochun Tang; Yuehua Ma; Jie Zhao; Hongyu Song (Environmental Science and Pollution Research, 2022)

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

Liver kinase B1 (LKB1) reduced inflammation and oxidative stress by regulating the AMPK/NLRP3 signaling pathway in LPS-induced lung injury - Yifeng Yue; Liwu Zong; Yongmin Chen; Nianhai Feng; Junxia Tang; Hongyu Xu; Meiling Zhao (Molecular & Cellular Toxicology, 2021)

Fatigue Damage Mechanism and Deformation Behaviour of Granite Under Ultrahigh-Frequency Cyclic Loading Conditions - Yu Zhou; Dajun Zhao; Bo Li; Hongyu Wang; Qiongqiong Tang; Zengzeng Zhang (Rock Mechanics and Rock Engineering, 2021)

Prevalence of GII.4 Sydney Norovirus Strains and Associated Factors of Acute Gastroenteritis in Children: 2019/2020 Season in Guangzhou, China - Lei Duan; Xiaohan Yang; Jia Xie; Wenli Zhan; Changbin Zhang; Hong Liu; Mengru Wei; Yuan Tang; Hongyu Zhao; Mingyong Luo (Food and Environmental Virology, 2021)
Norovirus, the leading cause of non-bacterial acute gastroenteritis (AGE) worldwide, is constantly mutating. Continuous monitoring of the evolution of epidemic genotypes and emergence of novel genotypes is, therefore, necessary. This study determined the prevalence and clinical characteristics of norovirus strains in AGE in Guangzhou, China in 2019/2020 season. This study included children aged 2–60 months diagnosed with AGE in Guangzhou Women and Children Hospital, from August 2019 to January 2020. Norovirus was detected by real-time polymerase chain reaction and clinical data were obtained. Genotyping and phylogenetic analyses were performed with partial gene sequence fragments located within the open reading frames 1 and 2. During the study period, 168 children (61.3% males) were confirmed as norovirus infectious AGE. The main symptoms were diarrhoea and vomiting and 38 patients (22.6%) had seizures. Norovirus was mainly prevalent in October and November, and GII.4 Sydney[P31] was the major genotype circulating in Guangzhou. The phylogenetic tree showed that the Guangzhou strains had high homology with the strains circulating in 2017–2019 worldwide. GII.4 Sydney was the main prevalent norovirus genotype in Guangzhou from August 2019 to January 2020, which had more severe diarrhoea than those of other genotypes. These findings provide a valuable reference for the prevention, control, and treatment of norovirus in the future.

Experimental study of the visible seepage characteristics and aperture measurement of rock fractures - Zheng Li; Jie Liu; Yan Zhang; Jianxiang Guo; Zhao Li; Hongyu Tang; Qian Shi (Arabian Journal of Geosciences, 2021)

Prediction and correction of in situ summer precipitation in Southwest China based on a downscaling method with the BCC_CSM - Qu Guo; Xiangwen Liu; Hongyu Tang; Yonghua Li (Theoretical and Applied Climatology, 2021)

Abdominal paracentesis drainage attenuates severe acute pancreatitis by enhancing cell apoptosis via PI3K/AKT signaling pathway - Chen Luo; Qilin Huang; Xiaohui Yuan; Yi Yang; Bing Wang; Zhu Huang; Lijun Tang; Hongyu Sun (Apoptosis, 2020)
Our previous studies have shown that abdominal paracentesis drainage (APD) is a safe and effective strategy for patients with severe acute pancreatitis (SAP). However, the underlying mechanisms behind APD treatment remain poorly understood. Given that apoptosis is a critical pathological response of SAP, we here aim to investigate the effect of APD on cell apoptosis in pancreatic tissues during SAP and to explore its potential molecular mechanism. SAP was induced by 5% sodium-taurocholate retrograde while APD group was inserted a drainage tube into the right lower abdomen of rats immediately after SAP induction. Histopathological staining, serum amylase, endotoxin and inflammatory mediators were measured. Cell apoptosis, apoptosis-related proteins and signaling pathway were also evaluated. Our results demonstrated that APD treatment significantly attenuated pancreatic damage and decreased the serum levels of amylase, endotoxin, TNF-α, IL-1 and IL-6 in rats with SAP. Notably, APD treatment enhanced cell apoptosis and reduced necrosis in pancreatic tissues, as evidenced by Tunnel staining, the increased pro-apoptosis proteins (Cleaved-caspase-3 and bax) and decreased anti-apoptosis protein (Bcl-2). Moreover, the effect of APD on cell apoptosis was further confirmed by the regulatory pathway of PI3K/AKT and NF-kB signaling pathway. These results suggest that APD attenuates the severity of SAP by enhancing cell apoptosis via suppressing PI3K/AKT signaling pathway. Our findings provide new insights for understanding the effectiveness of APD in patients with SAP.

Preparation, Characterization, and Properties of Inclusion Complexes of Balofloxacin with Cyclodextrins - Xiuyun Ren; Hongyun Qian; Peixiao Tang; Yuling Tang; Yuanyuan Liu; Hongyu Pu; Man Zhang; Ludan Zhao; Hui Li (AAPS PharmSciTech, 2019)

Performance of BCC-CSM Models with Different Horizontal Resolutions in Simulating Extreme Climate Events in China - Linxiao Wei; Xiaoge Xin; Chan Xiao; Yonghua Li; Yao Wu; Hongyu Tang (Journal of Meteorological Research, 2019)

Proteomics analysis of Schwann cell-derived exosomes: a novel therapeutic strategy for central nervous system injury - Zhijian Wei; Baoyou Fan; Han Ding; Yang Liu; Haoshuai Tang; Dayu Pan; Jiaxiao Shi; Pengyuan Zheng; Hongyu Shi; Heng Wu; Ang Li; Shiqing Feng (Molecular and Cellular Biochemistry, 2019)

Three-dimensional Forest growth simulation in virtual geographic environments - Liyu Tang; Xianmin Peng; Chongcheng Chen; Hongyu Huang; Ding Lin (Earth Science Informatics, 2019)

Trends in autumn rain of West China from 1961 to 2014 - Chi Zhang; Zunya Wang; Botao Zhou; Yonghua Li; Hongyu Tang; Bo Xiang (Theoretical and Applied Climatology, 2019)

Strand-specific RNA-seq analysis of the Acidithiobacillus ferrooxidans transcriptome in response to magnesium stress - Deping Tang; Jiangong Duan; Qiyu Gao; Yang Zhao; Yang Li; Peng Chen; Jianping Zhou; Zhengrong Wu; Ruixiang Xu; Hongyu Li (Archives of Microbiology, 2018)

Morphological and genetic characterization of a new cytoplasmic male sterility system (oxa CMS) in stem mustard (Brassica juncea) - Shuangping Heng; Sansan Liu; Chunxiu Xia; HongYu Tang; Fei Xie; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2018)

Anti-Collision Assessment and Prediction Considering Material Corrosion on an Offshore Protective Device - Ang Qiu; Xiangxi Han; Hongyu Qin; Wei Lin; Youhong Tang (Journal of Marine Science and Engineering, 2017)
Corrosion deterioration of steel can heavily degrade the performance of marine and offshore structures. A typical steel protective device, which has worked for a dozen years in a river estuary, is selected as the research object. Its current corrosion response is measured on site and its further corrosive response is predicted based on measurement data and the structure’s current state. Nonlinear finite element method is utilized to analyze the degradation of the protective device’s anti-collision performance. Meanwhile the rubber buffer effect has been investigated for its anti-collision on the protective device. A prediction method is proposed that can accurately forecast degradation of the anti-collision performance of a protective device as time progresses.

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

Determination and analysis of the dissipation and residue of cyprodinil and fludioxonil in grape and soil using a modified QuEChERS method - Wen Zhang; Hongyu Chen; Xinwei Han; Zaihui Yang; Mingming Tang; Jing Zhang; Song Zeng; Deyu Hu; Kankan Zhang (Environmental Monitoring and Assessment, 2015)

IGF1(CA)19 and IGFBP-3-202A/C Gene Polymorphism and Cancer Risk: A Meta-analysis - Hongyu Quan; Hao Tang; Li Fang; Jianjun Bi; Yunsheng Liu; Hongli Li (Cell Biochemistry and Biophysics, 2014)

Expression, Purification, and Characterization of an Iron Chaperon Protein CyaY from Acidithiobacillus ferrooxidans - Chenbing Ai; Hongyu Mo; Qian Chen; Yuandong Liu; Lin Tang; Juan Du; Jia Zeng (Current Microbiology, 2011)

Synthesis and primary evaluation of quinoxalinone derivatives as potent modulators of multidrug resistance - Hongyu Yuan; Xun Li; Xianjun Qu; Lirui Sun; Wenfang Xu; Wei Tang (Medicinal Chemistry Research, 2009)